2016
DOI: 10.5194/acp-16-9361-2016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seed aerosol surface area and oxidation rate on vapor wall deposition and SOA mass yields: a case study with <i>α</i>-pinene ozonolysis

Abstract: Abstract. Laboratory chambers, invaluable in atmospheric chemistry and aerosol formation studies, are subject to particle and vapor wall deposition, processes that need to be accounted for in order to accurately determine secondary organic aerosol (SOA) mass yields. Although particle wall deposition is reasonably well understood and usually accounted for, vapor wall deposition is less so. The effects of vapor wall deposition on SOA mass yields in chamber experiments can be constrained experimentally by increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 83 publications
(177 reference statements)
8
86
2
Order By: Relevance
“…These ELVOCs have been observed during both chamber and in situ measurements in Germany (Mutzel et al, 2015). Several studies showed the importance of nighttime SOA formation from MT via nitrate radical oxidation, resulting in the formation of organic nitrates (Pye et al, 2015;Bean and Ruiz, 2016;Xu et al, 2015;Nah et al, 2016). Pye et al (2010) showed the importance of reactive nitrogen and pointed out the fact that organic nitrate accounts for more than a half of the monoterpene oxidation products in the particle phase over the US.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…These ELVOCs have been observed during both chamber and in situ measurements in Germany (Mutzel et al, 2015). Several studies showed the importance of nighttime SOA formation from MT via nitrate radical oxidation, resulting in the formation of organic nitrates (Pye et al, 2015;Bean and Ruiz, 2016;Xu et al, 2015;Nah et al, 2016). Pye et al (2010) showed the importance of reactive nitrogen and pointed out the fact that organic nitrate accounts for more than a half of the monoterpene oxidation products in the particle phase over the US.…”
Section: Introductionmentioning
confidence: 97%
“…Organic nitrates are formed where biogenic VOCs and anthropogenic NO x sources interact (Pye et al, 2015;Xu et al, 2015;Bean and Ruiz, 2016;Nah et al, 2016). We used here the parameterisation of Pye et al (2015) to account for the formation of organic nitrate compounds from the oxidation by OH and NO 3 of MT.…”
Section: Organic Nitrates Formation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental measurements of SOA formation in laboratory Teflon chambers are influenced by deposition of both particles and vapors to the chamber walls, and evaluation of the SOA yield from VOC oxidation must take careful accounting for such wall losses (e.g., Zhang et al, 2014;Nah et al, 2017Nah et al, , 2016. We seek to assess the extent to which both vapor and particle deposition onto the entrance region and quartz wall of the flow tube is influential in flow tube reactor studies.…”
Section: Y Huang Et Al: the Caltech Photooxidation Flow Tube Reactormentioning
confidence: 99%
“…Second, it is likely that previous estimates of SOA yields from wellknown VOC precursors (e.g., toluene, xylene, alkanes, isoprene, terpenes) derived from smog chamber experiments were biased by unaccounted loss of semivolatile organic vapors to the chamber walls (Hildebrandt et al, 2009;Mat-B. N. Murphy et al: Comprehensive evaluation of CMAQ semivolatile POA sunaga and Ziemann, 2010; Loza et al, 2010;Yeh and Ziemann, 2014;Zhang et al, 2014Zhang et al, , 2015Cappa et al, 2016;Nah et al, 2016;Krechmer et al, 2016;Saha and Grieshop, 2016;Ma et al, 2017;Nah et al, 2017). The magnitude of this bias likely varies substantially among experimental systems (i.e., precursor and oxidant identity) and experimental conditions (e.g., seed concentration, relative humidity, temperature; Krechmer et al, 2016;Nah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%